To prevent the allergic disease: the dream of the allergist - Ciprandi, Giorgio; Licari, Amelia; Marseglia, Gian Luigi (Acta Biomedica Atenei Parmensis, 2020)
Allergen avoidance, allergen immunotherapy, IgE antagonists, biological medications, prevention and treatment of respiratory infections, probiotics, adapted formula, vitamins, and oligo-elements have been investigated as strategies in the prevention of allergic diseases. Promising findings were obtained. To prevent allergic diseases could be a dream that will be soon realized in clinical practice.